Innovative management by the industrial sector of the Republic of Kazakhstan in the conditions of digitalization: relevance and content - Sherimova, N.M. (BUKETOV BUSINESS REVIEW, 2019)
Qualitative changes, taking place in modern conditions, contain an innovative component in the management and tactics of production development. The intensive growth of innovation in the economy has acquired an all-encompassing character. Positive shifts in the industry are explained by the increase in their informational, intellectual, and innovative elements. All this determines the transformation in the management of business entities, namely the increasing role of innovative impact. In the article the innovative management by the industrial sector in the conditions of digitalization as one of the mechanisms to ensure the progressive development of the country's economy is considered. The originality of this article is to study the peculiarities of innovation management in the foreign experience in the modern conditions, in terms of the digital economy. The proposals on the main aspects of digitalization of the industrial sector of the economy and the prospects for its development are considered. The main directions of the system of implementation of innovative management methods by conducting a sound policy of digitalization for global changes in the field of innovation are presented, such as the creation of technology parks, research and production clusters, smart cities and other innovative projects. The features and successes in the management of innovation, which are achieved by domestic companies, were analyzed. Also the conclusions regarding the use of effective administrative tools for the purpose of permission of problems of management of innovative activity of the industrial enterprises are drawn.